Isolation and characterization of bacteriophage from environmental water samples specific for Klebsiella pneumoniae - Roy, Arka (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.